Pengaruh Variabel Makroekonomi Terhadap Pertumbuhan Sukuk Korporasi di Indonesia - kurniawan, kurniawan; Masitoh, Endang; Fajri, Rosa Nikmatul (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2020)
The capital market always experiences development over time. In addition to conventional capital markets, the Islamic capital market is also experiencing growth. This can be seen with the issuance of sukuk. Sukuk is an investment instrument based on sharia agreements, a country's economic condition has an important role in sukuk growth. The purpose of this research is to know and analyze the macroeconomic variable factors on the growth of corporate sukuk in Indonesia. This type of research is quantitative research with secondary data obtained from the official website of the Financial Services Authority. The research method uses multiple linear regression models. The results explained that macroeconomic variables such as inflation, exchange rates, money supply have an influence on the growth of corporate sukuk.